2012
DOI: 10.1007/s40261-012-0008-2
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime Cost-Utility Analyses of Deferasirox in Beta-Thalassaemia Patients with Chronic Iron Overload

Abstract: Higher drug acquisition costs for deferasirox are offset by the avoidance of infusion-related equipment costs. Combined with health benefits derived from an oral mode of administration and improved compliance, deferasirox has a high probability of being a cost-effective intervention compared with deferoxamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…A Markov structure was used based on the relevant clinical data (cardiac mortality and morbidity); this structure has been used in previous economic evaluations of iron chelation regimens [29, 30]. An annual cycle was chosen given the availability of annual mortality data; such a cycle has also previously been used in economic evaluations of iron chelation regimens [28].…”
Section: Methods: Economic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…A Markov structure was used based on the relevant clinical data (cardiac mortality and morbidity); this structure has been used in previous economic evaluations of iron chelation regimens [29, 30]. An annual cycle was chosen given the availability of annual mortality data; such a cycle has also previously been used in economic evaluations of iron chelation regimens [28].…”
Section: Methods: Economic Modelmentioning
confidence: 99%
“…Previous economic evaluations have focused on DFO and DFX, and have reported that DFX is cost effective compared with DFO, although none have used published adverse event (AE) rates [3, 28, 29]. However, DFP has been included in cost-effectiveness analysis in only one study, from a Thai perspective, which did not consider combination therapy [30].…”
Section: Introductionmentioning
confidence: 99%
“…This paper expands on the findings in the Karnon 2008 UK analysis to consider cost-utility of DFO and DFX when modeled over the long term and to include additional brief commentary on DFO-DFP combination therapy [32]. This updated analysis found that the higher drug costs for DFX were more than offset by the administration costs of DFO, and that DFX was cost-effective compared with either DFO monotherapy or DFO-DFP combination.…”
Section: Karnon Et Al Clinical Drug Investigation 2012mentioning
confidence: 82%
“…Overall, the authors concluded that DFX dominated DFO (i.e., resulted in lower net costs and higher quality-adjusted life-years) in the base case; this conclusion was robust to the multiple sensitivity analyses that were reported in the paper. The choice of a 1-year time horizon may make the findings less relevant in the context of a lifetime treatment; the investigators addressed this limitation in their follow-up paper [32], which is also discussed in this article. The limitations inherent in short time horizons might be less of a factor for decision makers in markets such as the US, where many private insurers experience high turnover rates.…”
Section: Karnon Et Al Current Medical Research and Opinions 2008mentioning
confidence: 99%
“…[18][19][20][21][22] The common results for the US 18 and UK 19,21 healthcare system perspectives on the cost effectiveness of oral DFX vs infusional DFO suggest that DFX is cost effective compared to standard chelation with DFO, while a different conclusion is reached by Luangasanatip et al 20 in Thailand. The two studies that perform a cost analysis of DFP 20,22 both suggest that DFP is the most cost-effective cure for the treatment of iron overload in b-thalassemia patients.…”
Section: Introductionmentioning
confidence: 99%